Wave propagation analysis of smart nanostructures - Ebrahimi, Farzad, 1979-; Dabbagh, Ali (Mechanical engineering) (Boca raton: CRC Press, 2020)
"Wave Propagation Analysis of Smart Nanostructures presents a mathematical framework for the wave propagation problem of small scale nanobeams and nanoplates manufactured from various materials including functionally graded composites, smart piezoelectric materials, smart magneto-electro-elastic materials, smart magnetostrictive materials, porous materials, and magnetostrictive materials. In this book, both classical and refined higher-order shear deformation beam and plate hypotheses will be employed to formulate the wave propagation problem using the well-known Hamilton's principle. Besides, the influences of small scale on the mechanical behaviors of the nanostructures will be covered using both nonlocal elasticity and nonlocal strain gradient elasticity theories. Impacts of various terms such as elastic springs of elastic foundation, damping coefficient of viscoelastic substrate, different types of temperature change, applied electric voltage and magnetic potential, and intensity of an external magnetic field on the dispersion curves of nanostructures will be included in this book in the framework of numerical examples"--
Includes bibliographical references and index.
Keywords: Nanostructured materials -- Mechanical properties; Smart materials -- Mechanical properties; Wave-motion, Theory of -- Mathematics